2017
DOI: 10.1038/s41598-017-01294-2
|View full text |Cite
|
Sign up to set email alerts
|

miR-301b~miR-130b—PPARγ axis underlies the adipogenic capacity of mesenchymal stem cells with different tissue origins

Abstract: Mesenchymal stem cells (MSCs) have been widely used in regenerative medicine and cellular therapy due to their multi-lineage differentiation potential and immunomodulatory function. The applicability of MSCs also depends on their cellular sources and in vivo functions. Here in this study, we systematically compared the morphologic characteristics, immunophenotypes and the adipogenic differentiation of MSCs derived from umbilical cord (UC), adipose tissue (Ad) and bone marrow (BM). We found that the three tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 45 publications
4
19
0
Order By: Relevance
“…Of the listed factors, a number of studies indicated that long-term in vitro culture and continuous passages were the prohibiting factor for phenotype and function of MSCs, yet the evidence was still lacking [21,22,31]. Currently, even though we and other investigators have compared the biological signatures of hUC-MSCs with hBM-MSCs or hAD-MSCs in some respects at the cellular level, few of the studies are further focusing on the distinctions at the molecular level [21,37]. Very recently, by utilizing single-cell transcriptomic analysis, Huang et al reported that the in vitro expanded hUC-MSCs showed heterogeneity in inflammatory cytokines and cell cycle stages [31], which was consistent with our data by whole-exome sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Of the listed factors, a number of studies indicated that long-term in vitro culture and continuous passages were the prohibiting factor for phenotype and function of MSCs, yet the evidence was still lacking [21,22,31]. Currently, even though we and other investigators have compared the biological signatures of hUC-MSCs with hBM-MSCs or hAD-MSCs in some respects at the cellular level, few of the studies are further focusing on the distinctions at the molecular level [21,37]. Very recently, by utilizing single-cell transcriptomic analysis, Huang et al reported that the in vitro expanded hUC-MSCs showed heterogeneity in inflammatory cytokines and cell cycle stages [31], which was consistent with our data by whole-exome sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…PPARγ is considered a master regulator of adipogenic fate decision 21 . Our previous work demonstrated that PPARγ expression positively correlates with the adipogenic capacity of MSCs with different tissue origins 22 . In this study, we further validated the regulatory role of PPARγ with its two specific shRNAs in the adipogenesis of BM-MSCs.…”
Section: Resultsmentioning
confidence: 54%
“…Adipogenic differentiation was performed according to the method described elsewhere with minor modifications . The MSCs were seeded into 12‐well plates.…”
Section: Methodsmentioning
confidence: 99%